School staff and teachers during the second year of COVID-19: Higher anxiety symptoms, higher psychological distress, and poorer mental health compared to the general population - Sarah M. Hutchison; Allison Watts; Anne Gadermann; Eva Oberle; Tim F. Oberlander; Pascal M. Lavoie; Louise C. Mâsse (Journal of Affective Disorders Reports, 2022)
Background: The aim of this study was to: 1) assess mental health symptoms in Canadian school staff during the second year of the pandemic (Spring 2021) and compare these same outcomes to national representative samples, and 2: examine whether the number of hours of direct contact with students was a significant predictor of anxiety symptoms. Methods: Online data on anxiety symptoms, psychological distress, overall mental health, and demographic information was collected from 2,305 school staff in the greater Vancouver area between February 3 and June 18, 2021, as part of a seroprevalence study. Results: School staff reported significantly higher anxiety symptoms than a national representative survey in Spring 2021 and higher exposure contact time with students was significantly associated with anxiety symptoms, in addition to sex and age, but not level of education and ethnicity. School staff also reported poorer mental health and higher levels of psychological distress compared to pre-pandemic population measures. Limitations: Cross-sectional design, self-report measures. Conclusions: These results show that priorities to reduce mental health challenges are critical during a public health crisis, not only at the beginning, but also one year later. Ongoing proactive prevention and intervention strategies for school staff are warranted.